Cereal Straw As A Food Supplement Processed By Solid-State Fermentation (2024)
Solid state fermentation is a process in which the metabolism of lactic acid bacteria is used mainly to obtain food products with greater nutritional value. Recently, it has been possible to potentiate substrates with low nutritional compositions as pos-harvest residues, making them more digestible for animals. This study aimed to evaluate the usefulness of solid-state fermentation in enhancing the nutritional value of cereal straw and the effect of the time and percentage of inclusion of this residue in the fermentation. For this, two diets were prepared, one with 10% inclusion of cereal straw and another with 20%, potatoes, alfalfa flour, mineral premix, urea, molasses, sodium sulfate, calcium carbonate and microbial preparation enriched with lactic acid bacteria (LAB) were added. The products were subjected to two fermentation times (24 and 48 hours) at a constant temperature of 20°C. The effect of fermentation time and the percentage of inclusion of fibrous plant material on the pH, dry matter, humidity, crude protein, ash, ethereal extract, neutral and acid detergent fiber, hemicellulose, organic matter, in situ digestibility of the dry matter and microbiology were analyzed. After 48 hours of fermentation, it was evident that an inclusion percentage of 20% favors a decrease in pH, and increase the count of lactic acid bacteria, the amount of crude protein, ash and neutral detergent fiber, parameters that indicate the quality of the food, digestibility and usefulness to be supplied as a diet to sheep.